: Effects of activated charcoal on medium-term conservation of yam (Dioscorea spp.) cultivated in Benin - CACAÏ, Gilles Habib Todjro (My University, 2017)
The effects of activated charcoal were tested on medium term conservation of yams cultivated through tissue culture techniques. Galzy glutamine basic medium and that supplemented with 3 g/l activated charcoal were used. Growth parameters such as number of leaves, height of stem, number of nodes and length of the main root are evaluated on plantlets after 20 months. The test T of Student Newman and Keuls (SNK) with two independent variables was used for the comparison of means with Minitab 16 software. Plantlets obtained in the control medium faded and presented a high number. The length of internodes obtained from the medium treated with activated charcoal had a length relatively greater than the control medium with increase of 33%. Probabilities (P = 0.001) associated with the T-test of equality of means of leaves, the height of stem and the length of internodes are lower than 0.05 but there was no significant difference between the number of nodes, length of internodes, number of roots, and length of the main root of plantlets obtained in both media at 5%. In addition, tests of correlation (Pearson) in the control medium revealed the existence of a highly significant link (P <0.001) between the number of nodes and number of leaves. In treated medium, there was a highly significant link (P <0.004) between the length of the stem and number of leaves; the height of the stem and length of the main root (P <0.001). Activated charcoal facilitates conservation and constitutes an alternative of conservation of yam. These results may be used to realize in vitro collection of different genotypes of yam cultivated in Benin.
Keywords: In vitro conservation; plantlets; yam; activated charcoal.